Adaptability parameters of spring barley according to the trait ‘1000-grain weight’ in the Rostov region - R. N. Bragin (Зерновое хозяйство России, 2025)
Spring barley, being one of the leading crops in agricultural production in Russia, is characterized by increased adaptability and high resistance to abiotic and biotic stress factors. When studying and estimating spring barley samples, it is important to understand the impact on the adaptive capacity of varieties not only according to the trait ‘productivity’, but also according to the trait ‘1000-grain weight’. The purpose of the current work was to study the adaptive capacity of spring barley varieties according to the trait ‘1000-grain weight’ in the Rostov region in 2019–2021. The number of studied varieties was 29 pcs., 4-fold repetition, sown after such forecrops as sunflower, peas and maize for grain. The standard variety was ‘Ratnik’, with the area of the accounting plot being 10 m². The largest 1000-grain weight of spring barley was obtained from the varieties ‘Zernogradsky 73’, ‘Priazovsky 9’, ‘Azimut’, ‘Zernogradsky 1701’, ‘Arkan’, ‘Zernogradsky 1754’ with all forecrops. The most variable was the variety ‘Zernogradskiy 1721’ with a variability coefficient V = 10.42…12.34 %. High stress resistance was identified in the varieties ‘Zernogradskiy 1754’ ((Ymin–Ymax) = -0.1…-5.5), ‘Zernogradskiy 1752’ ((Ymin–Ymax) = -0.3…-2.3) and ‘Azimut’ ((Ymin–Ymax) = -0.7…-5.8). The most genetically flexible varieties were ‘Zernogradskiy 1721’ ((Ymin+Ymax)/2 = 41.5…49.6) and ‘Azimut’ ((Ymin+Ymax)/2 = 40.7…51.9). The variety ‘Zernogradskiy 1721’ had the best coefficient of responsiveness (Kr. = 1.15…1.19). The varieties ‘Azimut’ and ‘Arkan’ turned to be highly adaptable and coarse-grained with all forecrops and in all years.